2017
DOI: 10.1038/s41598-017-08295-1
|View full text |Cite
|
Sign up to set email alerts
|

Triglycerides and Open Angle Glaucoma – A Meta-analysis with meta-regression

Abstract: Although intraocular pressure is the main the risk factor for the development of glaucoma, other risk factors such as vascular dysfunction might play an additional pathogenic role. Hypertriglyceridemia, which may lead to vascular dysfunction, has been implicated in the development of glaucoma. The objective of this meta-analysis was to investigate the association of triglyceride levels with the risk of glaucoma in case-control studies. Seventeen case-control studies were included investigating the difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
3
24
0
1
Order By: Relevance
“…A missense variant in ADAMTSL1 was associated with a complex phenotype including congenital glaucoma, craniofacial, and other systemic features 26 . Because lipid and fatty acid profiles in blood are associated with glaucoma 27 , 28 , these results support the hypothesis that ADAMTSL1 plays important roles in lipid (fatty acid) metabolism. In fact, previous GWASs and other studies reported that the ADAMTSL1 locus is associated with many kinds of phenotypes, including cholesterol (Supplementary Data 4 ).…”
Section: Resultssupporting
confidence: 75%
“…A missense variant in ADAMTSL1 was associated with a complex phenotype including congenital glaucoma, craniofacial, and other systemic features 26 . Because lipid and fatty acid profiles in blood are associated with glaucoma 27 , 28 , these results support the hypothesis that ADAMTSL1 plays important roles in lipid (fatty acid) metabolism. In fact, previous GWASs and other studies reported that the ADAMTSL1 locus is associated with many kinds of phenotypes, including cholesterol (Supplementary Data 4 ).…”
Section: Resultssupporting
confidence: 75%
“…A metaanalysis found that the mean triglyce ride levels in glaucoma patients were higher by approximately 14 mg/dL than in general population. Although this was a sta tistically significant finding, it is unclear whether it has clinical importance and warrants further research (11). On the other hand, glaucoma treatment, especially beta blockers, are su spected of increasing triglyceride levels.…”
Section: Triglycerides and Smokingmentioning
confidence: 78%
“…On the other hand, glaucoma treatment, especially beta blockers, are su spected of increasing triglyceride levels. Additionally, different metaanalysis showed that statin use was associated with a re duced incidence of glaucoma (11).…”
Section: Triglycerides and Smokingmentioning
confidence: 99%
“…[7] Hypertriglyceridemia causes vascular dysfunction that leads to increased blood viscosity which causes elevation of episcleral venous pressure. [28] Several case-control studies report a significant association of triglycerides with glaucoma and with intraocular pressure. [5910]…”
Section: Discussionmentioning
confidence: 99%
“…[1] Hypertriglyceridemia is one such metabolic factor, it causes vascular dysfunction that can further lead to glaucoma. [2] So, a thorough ocular and systemic examination can help us to treat the patient rationally.…”
mentioning
confidence: 99%